Real-world treatment patterns of patients with major depressive disorder treated with Auvelity in the United States. - Muzyk, Andrew; Syed, Fatima Zahara; Zhou, Huanxue; Cong, Junjun; Tabuteau, Herriot; Zhao, Yang (Journal of Medical Economics)
Aims: Major depressive disorder (MDD) is a prevalent, chronic disorder. Auvelity (dextromethorphan-bupropion) is a novel, oral N-methyl-D-aspartate (NMDA) receptor antagonist and sigma-1 receptor agonist approved (August 2022) by the FDA for treating MDD in adults. This is the first analysis on real-world Auvelity usage in the United States. Methods: Adult patients initiating Auvelity in the Symphony IDV databases by September 2023 were identified (index date: the first Auvelity claim). Patients had continuous eligibility over the 12-month pre-index period and ≥1 MDD diagnosis (ICD-10-CM codes: F32.*, F33.*) over the 5-year pre-index period. Demographic and clinical characteristics, comorbidities, prior MDD-related medications, and Auvelity initiation status were assessed. Results: This analysis included 22,288 patients with MDD treated with Auvelity (mean age 45.1 years; 68.1% women); 40.0% lived in the South and 58.5% had commercial insurance. Comorbidities included mental health disorders (53.5%; 47.6% had anxiety disorders). Overall, 83.7% of the patients had received treatment with selective serotonin reuptake inhibitors (SSRIs; 54.9%), the norepinephrine-dopamine reuptake inhibitor (NDRI [bupropion]; 40.4%), and/or serotonin-norepinephrine reuptake inhibitors (SNRIs; 35.9%) over the 12-month pre-index period. The last MDD-related treatment prior to Auvelity comprised SSRI (22.4%), SNRI (13.2%), and NDRI (12.8%) monotherapies; 294 (1.3%) patients received esketamine. In total, 6,418 (28.8%) patients initiated Auvelity as monotherapy vs 15,870 (71.2%) as an add-on; Auvelity was most frequently added to an SSRI alone (10.7%) or SNRI alone (6.5%). A total of 2,254 (10.1%) patients initiated Auvelity without prior treatment in the 12-month pre-index period. Limitations: Incomplete data due to reporting; diagnoses captured subject to coding error; and limited generalizability to other populations. Conclusions: Using a large demographically distributed claims database, 22,288 patients with MDD initiated Auvelity within a year of its approval; 10.1% were treatment-naïve and 28.8% initiated Auvelity as monotherapy. Most patients had mental health-related comorbidities and attempted various MDD-related treatments prior to Auvelity. PLAIN LANGUAGE SUMMARY: Major depressive disorder (medical terminology for "depression") is a common medical condition that makes people feel persistently sad or hopeless, affecting their ability to handle daily activities. Effective treatment, which may include medication, is crucial for improving their quality of life. This study explores how people in the United States use a new medication called Auvelity to treat depression. Researchers reviewed the medical records of over 22,000 adults with depression, looking at their age, gender, location, type of health insurance, other health conditions, and use of other depression medications. The study focused on people who started using Auvelity in the first year after its Food and Drug Administration (FDA) approval. On average, Auvelity users were 45 years old. They lived across various regions of the US, had different types of health insurance, and over two-thirds were women. Many Auvelity users had other mental health disorders, including anxiety. Most had tried different types of medications for depression in the previous year, while about 10% had not used any other depression medicines in the previous year. When starting Auvelity, almost one-third of patients used it as their only depression medicine. Over two-thirds of patients started Auvelity alongside another depression medicine. Initial Auvelity prescriptions were issued by a diverse range of medical professionals, including psychiatrists, primary care physicians, nurse practitioners, and physician assistants. These findings provide valuable insights into how this new medicine is used in real life and can inform treatment decisions of healthcare providers who help manage depression in their patients.